Terms of endearment : Hollywood romantic comedy of the 1980s and 1990s - Evans, Peter William; Deleyto, Celestino (Edinburgh University Press, 1998)
Using a wide range of popular mainstream films, this book looks at how recent cultural discourses on gender and sexuality have found their way into the apparently inflexible structure of romantic comedy.